Genetic introgression of hybrid Rhododendron x intermedium Tausch is habitat mediated: Evidences from south-eastern Alps (Italy). (3rd May 2016) - Bruni, I.; De Mattia, F.; Fluch, S.; Ferrari, C.; Corazza, M.; Dinelli, E.; Labra, M.
Abstract : Hybridization between Rhododendron ferrugineum L. and R. hirsutum L. in south-eastern Alps was examined in order to (i) evaluate the breeding direction and the extent of backcrossing between hybrids and the parental species, (ii) define which processes facilitate speciation and maintain species identities and (iii) clarify the role of rock geochemistry in hybridization events. Individuals of three hybrid populations were analysed by morphological and molecular markers. The internal transcribed spacer and trnH–psbA distinguished the parental species and F1 hybrids while only the simple sequence repeat markers recognized genotype classes: F, H, F1, F2, BxF (backcross to R. ferrugineum ) and BxH (backcross to R. hirsutum ). Combining morphological and molecular data, we found that the tested populations had complex genetic structure: the F1 individuals produce F2 hybrids and backcross to parental species. Due to R. hirsutum phenology, most backcrossing events were with this parental species (asymmetric hybridization). Geochemical analyses indicate that alkaline soil conditions linked to calcareous dolomitic rocks promoted the genetic assimilation of R. hirsutum. In addition, R. x intermedium shows a higher edaphic adaptation than R. hirsutum as it can be found on a wide range of calcareous-dolomitic rocks as well as on weakly acidic soils of natural or anthropogenic origin.